Effect of 4% and 15% moringa leaf extract gel on gingival wound healing in rats - Ramadhany, Eka Pramudita; Ambarawati, I Gusti Agung Dyah; Musyaffa, Muhammad Rafif (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Traumatic dental procedures such as incisions and gingival flaps are the leading causes of injury to the gingival structure. One of natural ingredients that can potentially accelerate the wound healing process is Moringa leaves Moringa oleifera). Moringa leaf has several active compounds, one of which is flavonoids, which can be an antiinflammatory and antibacterial agent, and increase collagen synthesis. A randomized posttest-only control-group design was used in this study. 48 wistar rats were categorized into four groups: CMC-Na gel, hyaluronic acid, 4% Moringa leaf extract gel, and 15% Moringa leaf extract gel. The samples were then euthanized on days 1, 3, 5, and 7. The two-way ANOVA test described significant differences (p < 0.05) for all the components of the observation (neutrophils, fibroblasts, angiogenesis, and epithelial thickness). The lowest mean number of neutrophils, the highest mean number of fibroblasts, and the highest mean of angiogenesis were found in the 15% Moringa extract group on the 7th day. The highest mean epithelial thickness was found in the use of 4% Moringa extract on the 5thday. The microscopic images showed that the treatment group gained more effective wound healing processes than the control group. The microscopic image showed that, in terms of neutrophils, fibroblasts, and angiogenesis, 15% Moringa extract was more effective for wound healing compared to 4% Moringa extract.